2018
DOI: 10.1177/2168479017738979
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Safety Profile Assessment of Oncolytic Virus Therapy Based on Clinical Trials

Abstract: Oncolytic virus therapy (OVT) represents a new class of therapeutic agents in cancer treatment. The molecular and cellular mechanisms of action of OVTs have been evaluated in nonclinical/clinical phase trials. Various genetically modified viruses have been developed as oncolytic agents, and the first approval of an OVT for clinical use was issued by the US Food and Drug Administration in 2015. In this context, more and more clinical development of OVTs is anticipated in the future. This article provides a risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The most common side effects were fatigue, nausea/vomiting, chills, and pain, all well-known infection-related symptoms. 19 Our data with Celyvir are similar in human and canine patients, with excellent tolerance of the treatment in most cases, resulting in no clinical secondary effects. However, there is a lack of knowledge about the biodistribution of the viruses after administration in patients.…”
Section: Discussionsupporting
confidence: 61%
“…The most common side effects were fatigue, nausea/vomiting, chills, and pain, all well-known infection-related symptoms. 19 Our data with Celyvir are similar in human and canine patients, with excellent tolerance of the treatment in most cases, resulting in no clinical secondary effects. However, there is a lack of knowledge about the biodistribution of the viruses after administration in patients.…”
Section: Discussionsupporting
confidence: 61%
“…A multitude of viruses from vesicular stomatitis virus, vaccinia virus or adenovirus are at various stages in clinical trials and most of them have a remarkable safety profile. Most side effects are infection-related or nausea and are easily manageable [36]. At preclinical level, it has been shown that oncolytic adenoviruses are successful in treating MIBC [37].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was recently shown that a low dose of 10 4 PFUs of CF33 in a preclinical flank setting slowed pancreatic tumor progression without measurable toxicities associated with virotherapy. 25 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…For example, it was recently shown that a low dose of 10 4 PFUs of CF33 in a preclinical flank setting slowed pancreatic tumor progression without measurable toxicities associated with virotherapy. 25,37 We have previously shown that the HB1.F3.CD cell line enhances adenoviral delivery to brain and peritoneal cancers; however, HB1.F3.CD-encapsulated pox virus delivery was not tested. In the current study, we utilized a research lot of HB1.F3.CD, equivalent to the clinical lot used in the glioma clinical trial (ClinicalTrials.gov: NCT03072134) to package CF33.…”
Section: Discussionmentioning
confidence: 99%